Loss of Notch dimerization perturbs intestinal homeostasis by a mechanism involving HDAC activity. - Quanhui Dai; Kristina Preusse; Danni Yu; Rhett A Kovall; Konrad Thorner; Xinhua Lin; Raphael Kopan (PLoS Genetics)
A tri-protein complex containing NICD, RBPj and MAML1 binds DNA as monomer or as cooperative dimers to regulate transcription. Mice expressing Notch dimerization-deficient alleles (NDD) of Notch1 and Notch2 are sensitized to environmental insults but otherwise develop and age normally. Transcriptomic analysis of colonic spheroids uncovered no evidence of dimer-dependent target gene miss-regulation, confirmed impaired stem cell maintenance in-vitro, and discovered an elevated signature of epithelial innate immune response to symbionts, a likely underlying cause for heightened sensitivity in NDD mice. TurboID followed by quantitative nano-spray MS/MS mass-spectrometry analyses in a human colon carcinoma cell line expressing either NOTCH2DD or NOTCH2 revealed an unbalanced interactome, with reduced interaction of NOTCH2DD with the transcription machinery but relatively preserved interaction with the HDAC2 interactome suggesting modulation via cooperativity. To ask if HDAC2 activity contributes to Notch loss-of-function phenotypes, we used the HDAC2 inhibitor Valproic acid (VPA) and discovered it could prevent the intestinal consequences of NDD and gamma secretase inhibitors (DBZ or DAPT) treatment in mice and spheroids, suggesting synergy between HDAC activity and pro-differentiation program in intestinal stem cells.